Evaluation of Microleakage by Gas Permeability and Marginal Adaptation of MTA and Biodentine™ Apical Plugs: In Vitro Study - Brenes-Valverde DDS, Karen (2017)
The endodontic treatment of teeth with incomplete development is always a complex task. Nowadays, biomaterials such as bioceramics offers promising clinical evidence that supports its use. However, the standardization of its use for apexification purpose still needs a deeper understanding of the materials’ behavior. The aim of this investigation was to evaluate the marginal adaptability and microleakage by gas permeability of MTA and Biodentine™ apical plugs in an in vitro model. Materials and methods: Twenty-four single rooted human teeth were selected according to previously stablished inclusion criteria. All samples were prepared obtaining standard cylindrical internal canals with a diameter of 1.3 mm. Root canals were gently rinsed using 5.25% sodium hypochlorite and EDTA 17%. The apical 3mm and remaining coronal dental structure were sectioned to obtain 10mm roots. Roots were randomly assigned to 3 different groups as follows: GROUP A: MTA (n=10), GROUP B: Biodentine™ (n=10) and Group C: Control (positive n=1, negative n=3). MTA and Biodentine™ were prepared according to manufacturer’s indications, and apical plugs of 4mm were passively placed in the correspondent teeth. All samples were stored in saline solution for 7 days at 37°C before evaluation. Samples were mounted in cylindrical sample-holders using epoxy resin. Microleakage was evaluated with an automatic permeability detector that calculates nitrogen diffusion between the material-root interphase. After microleakage evaluation, the samples were recovered and analyzed by scanning electron microscopy (SEM). Microleakage results were analyzed using Chi-square and adaptation was evaluated with a descriptive analysis. Results: None of the evaluated materials completely avoided the nitrogen microleakage (positive leakage of 10% and 20% of samples for MTA and Biodentine™ respectively); with no statistical significant difference between groups (p=0.527).  All apical plugs showed good adaptation under SEM, at 30x, 200x, 1000x and 2500x; with microscopical structures similar to previous reports. Conclusions: Both bioceramics behave similar when used as apical barriers to avoid permeability, with acceptable marginal adaptation. Further in vivo studies are needed to validate these results.